Effect of cyclic wetting and drying of restrained mortar specimens - Blakey, F. A. (Frank A.) (Report C (CSIRO. Division of Building Research), 1958)
Tests were done on small bars of cement mortar in which the shrinkage was restrained by a centrally placed steel rod, to compare the behaviour of the mortar under cyclic humidity conditions with the behaviour under uniform drying conditions. It is shown that the cracking strain is independent of water/cement ratio, but that this strain does increase with time. The cyclic treatment chosen was much less severe than the uniform drying conditions.